Polipropileno modificado com semicondutores a base de prata: compósitos com alta potencialidade contra SARS-CoV-2 e outros patógenos - Ribeiro, Lara Kelly (Universidade Federal de São Carlos, 2023)
The worldwide outbreak of the coronavirus (COVID-19) pandemic and other emerging infections is difficult and sometimes impossible to treat, making them one of the major public health issues of recent times. It is noteworthy that Ag based semiconductors can help to orchestrate several strategies to combat this serious social problem. In this thesis, we present the synthesis of Ag3PO4, α Ag2WO4, β-Ag2MoO4 and Ag2CrO4 and their immobilization in polypropylene in amounts of 0.5, 1.0 and 3.0% (w/w), respectively. Synthesized materials were characterized by XRD, Raman spectroscopy, FTIR spectroscopy, AFM, UV-vis spectroscopy, rheology, SEM and contact angle to confirm their structural integrity. The activity of the composites was investigated against the Gram negative bacteria Escherichia coli, the Gram-positive bacteria Staphylococcus aureus and the fungus Candida albicans. The best antimicrobial efficiency was obtained by the composite with α-Ag2WO4, which completely eliminated microorganisms within 4 h of exposure. The composites were also tested for inhibition of the SARS-CoV-2 virus, showing antiviral efficiency greater than 98% in just 10 min. Furthermore, based on the results of first principles calculations at the density functional level, a plausible reaction mechanism for the initial events associated with the generation of both hydroxyl radicals •OH and superoxide radical anion •O2– on the more reactive surface (110) of the Ag3PO4 semiconductor. The stability of the antimicrobial activity was evaluated, resulting in constant inhibition, even after the aging of the material. The antimicrobial activity of the compounds was attributed to the production of reactive oxygen species by semiconductors, which can induce high local oxidative stress, causing the death of these microorganisms. Ag/PP-based semiconductor composites have proven to be an attractive outlet for providing humans with a broad spectrum of biocidal activity.

El brote mundial de la pandemia de coronavirus (COVID-19) y otras infecciones emergentes son difíciles y, a veces, imposibles de tratar, lo que las convierte en uno de los principales problemas de salud pública de los últimos tiempos. Cabe señalar que los semiconductores basados en Ag pueden ayudar a orquestar varias estrategias para combatir este grave problema social. En esta tesis doctoral presentamos la síntesis de Ag3PO4, α-Ag2WO4, β-Ag2MoO4 y Ag2CrO4 y su inmovilización en polipropileno en cantidades de 0.5, 1.0 y 3.0% en peso, respectivamente. Los materiales fabricados se caracterizaron por XRD, espectroscopia Raman, espectroscopia FTIR, AFM, espectroscopia UV-vis, reología, SEM y ángulo de contacto para confirmar su integridad estructural. La actividad de los compuestos se investigó contra la bacteria Gram-negativa Escherichia coli, la bacteria Gram-positiva Staphylococcus aureus y el hongo Candida albicans. La mejor eficacia antimicrobiana se obtuvo para el composite α-Ag2WO4, que eliminó por completo los microorganismos a las 4 h de exposición. Los composites también se probaron para la inhibición del virus SARS-CoV-2, mostrando una eficacia antiviral superior al 98 % en solo 10 minutos. Además, en base a los resultados de los cálculos DFT (teoría de funcional de densidad), se ha propuesto un mecanismo de reacción plausible para los eventos iniciales asociados con la generación de radicales hidroxilos •OH y anión radical superóxido •O2– en la superficie más reactiva (110) del semiconductor Ag3PO4. Se evaluó la estabilidad de la actividad antimicrobiana, resultando en una inhibición constante, incluso después del envejecimiento del material. La actividad antimicrobiana de los compuestos se atribuyó a la producción de especies reactivas de oxígeno por parte de los semiconductores, que pueden inducir un elevado estrés oxidativo local, provocando la muerte de estos microorganismos. Los compuestos semiconductores basados en Ag/PP han demostrado ser una alternativa atractiva para proporcionar a los seres humanos un amplio espectro de actividad biocida.
Polypropylene modified with silver-based semiconductors: composites with high potential against SARS-CoV-2 and other pathogens
Polipropileno modificado con semiconductores de plata: composites con alto potencial contra el SARS-CoV-2 y otros patógenos
Keywords: Compósitos; Polipropileno; Prata; Biocida; SARS-CoV-2; Composites; Silver; Polypropylene; Biocide; SARS-CoV-2; Composites; Plata; Polipropileno; Biocida; SARS-CoV-2; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA